Graphene oxide scaffolds promote functional improvements mediated by scaffold-invading axons in thoracic transected rats - Marta Zaforas; Esther Benayas; Raquel Madroñero-Mariscal; Ana Domínguez-Bajo; Elena Fernández-López; Yasmina Hernández-Martín; Ankor González-Mayorga; Elena Alonso-Calviño; Eduardo R. Hernández; Elisa López-Dolado; Juliana M. Rosa; Juan Aguilar; et al. (Bioactive Materials)
Millions of patients and their caretakers live and deal with the devastating consequences of spinal cord injury (SCI) worldwide. Despite outstanding advances in the field to both understand and tackle these pathologies, a cure for SCI patients, with their peculiar characteristics, is still a mirage. One of the most promising therapeutic strategies to date for these patients involves the use of epidural electrical stimulation. In this context, electrically active materials such as graphene and its derivates become particularly interesting. Indeed, solid evidence of their capacity to closely interact with neural cells and networks is growing. Encouraged by previous findings in our laboratory on the exploration of 3D porous reduced graphene oxide (rGO) scaffolds in chronic cervical hemisected rats (C6), herein we report their neuro-reparative properties when chronically implanted in complete transected rats (T9-T10), in which no preserved contralateral neural networks can assist in any observed recovery. Electrophysiological recordings from brainstem regions show antidromic activation of a small population of neurons in response to electrical stimulation caudal to the injury. These neurons are located in the Gigantocellular nucleus of reticular formation and vestibular nuclei, both regions directly related to motor functions. Together with histological features at the lesion site, such as more abundant and larger blood vessels and more abundant, longer and more homogeneously distributed axons, our results corroborate that rGO scaffolds create a permissive environment that allows the invasion of functional axonic processes from neurons located in brainstem nuclei with motor function in a rat model of complete thoracic transection. Additionally, behavioral tests evidence that these scaffolds play an important role in whole-body mechanical stabilization (postural control) proved by the absence of scoliosis, a higher trunk stability and a larger cervico-thoraco-lumbar movement range in rGO-implanted rats.